INCREASE IN ORDER VOLUME AND TOTAL REVENUE OF PHARMACEUTICAL WHOLESALERS THROUGH THE IMPLEMENTATION OF E-COMMERCE - I Putu Sudiatmika Widnyana; Titien Siwi Hartayu (RADJA PUBLIKA, 2026)
Pharmaceutical Pharmaceutical Wholesalers play an essential role in ensuring the availability of medicines within the healthcare service system; however, their distribution performance is often constrained by conventional sales mechanisms. The implementation of e-commerce is expected to improve managerial efficiency and support sales performance in pharmaceutical distribution. This study aimed to assess the impact of e-commerce implementation on increasing order volume and total revenue at the pharmaceutical wholesaler PT. Wahana Fajar Utama in Bali. A quasi-experimental study with a one-group pretest–posttest design was conducted by analyzing transaction data for three months before and three months after the implementation of e-commerce. Data were analyzed using the Shapiro–Wilk normality test (p > 0,05) and the Paired Sample T-Test. The results showed an increase in the average monthly order volume from 194 to 256 (32%) and an increase in the average monthly revenue from IDR 264,723,293 to IDR 396,445,539 (49.7%). Statistical analysis indicated significant differences in both order volume (p value=0.034) and revenue (p value=0.018) before and after the intervention. The implementation of e-commerce was proven to significantly increase order volume and total sales revenue at PT. Wahana Fajar Utama.